Readaptation of Malay vernacular architecture for indoor thermal comfort in modern masjids towards a sustainable design - Mohd Nawayai, Siti Salwana; Denan, Zuraini; Abdul Majid, Noor Hanita (Malaysian Institute Of Planners, 2020)
The earlier masjid architectural styles were similar to Malay vernacular houses and evolved with the introduction of the modernist style. This resulted in increased energy consumption. Hence, a proper set of thermal comfort is important to provide a suitable environment for the masjid’s occupants. The vernacular characteristics in the passive designs have caused designers to find solutions towards sustainable designs. Therefore, designing a good thermal performance building can be done by readapting the Malay vernacular architecture and passive design strategies for modern masjids. This paper is aimed to document the literature and potential case studies in identifying the relationship between the design of Malay vernacular and thermal comfort elements in a hot and humid climate. The outcome is to formularize requirements of thermal comfort in Malay vernacular masjids based on four major factors namely i) architectural qualities, ii) construction systems, iii) structural components and iv) non-structural components. The research is intended to change the approach of future designers to become more sustainable based on the application of passive designs that suit the climatic condition of Malaysia.